LUNA: Journey from Ancient Times to Modern World (Homoeopathy for All, 2024)
Energy is a capacity of doing work  at spiritual as well as physical level.  Homoeopathy treats patient as a  whole on the basis of law of similia.  From the ancient times to till today,  moon is the important part of the  human society and its days to day  living. Luna is one of the natural  sources derived Imponderabilia  which have a diverse affinity for the  human organism.
Keywords: Energy; Holistic ap proach; Homoeopathy; Impondera bilia; Luna; Moon,; Rays